Accreditation Preparation System For Private Higher Education Institution - Berahim, Anuar (2005)
This report discusses the importance of information technology in facilitating the preparation of accreditation documentation which all Private Higher Education Institutions (PHEIs) in Malaysia must adhere to. This report also studies and proposes how such documents can be gathered, maintained and updated minus the laborious effort and heavy time consumption.